Work life balance and perception on job performance among female lecturers of Business Management Faculty at UiTM Melaka, Kampus Bandaraya / Nur Azlin Abdul Hamid and Nurul Nabilah Is’ad - Abdul Hamid, Nur Azlin; Is’ad, Nurul Nabilah (2015)
This study focuses on female lecturers of Business Management Faculty in UiTM Melaka, Kampus Bandaraya on how they achieve work life balance and perception on job performance. The female lecturers at UiTM Melaka, Kampus Bandaraya become respondents of this research because their working schedule and they facing more conflict between work and family or personal commitment especially for the married lecturers. This is because some of the lecturers need to work overtime especially during hectic week which is at the end of the semester but in the same time the lecturers need to finish their syllabus and focus on final exam. Whether public or private sector employees, they have their own problems especially for female employees that work in variety of work schedule. The researchers focus on female because nowadays, work life balance issues become one of the important issue that need to be discuss in seriously especially in order to make family free from any disruption and to make sure the family well-being are guaranteed. There are some cases arise which related to female. This can be proven where there are cases more towards the female employees such as divorce. The Malay Mail Online on March, 2014 reported that in 2012, a number of 56,760 divorces were recorded and according to statistics provided by the Syariah Judiciary Department Malaysia in 2013, numbers of 49,311 Muslim couples getting divorced are recorded. Besides, statistics also show that divorce rate is as high as 22% in Malaysia, and the number will keep increasing from year to year especially among Muslim couples (Sin Chew Daily, 2014). Thus, it shows one of the causes for this problem is unable achieving work life balance among female. This study also will analyze important issues as focused by the researchers that relate to the female’s work life balance such as work stress and flexible working arrangements. Work stress will able to influence the health of the employees. Then, flexible working arrangements is need because demand from the job and for development of economy in Malaysia. Indirectly, these factors will effect on their job performance as a lecture. Furthermore, this study also will investigate on how these work life balance and its factors able to give effect and influence their job performance as a lecture.